2005
DOI: 10.12968/npre.2005.3.5.19853
|View full text |Cite
|
Sign up to set email alerts
|

Non-medical prescribing in an outpatient setting: renal services

Abstract: Patients with chronic disease are increasingly managed by nurse practitioners and nurse prescribing affords the full completion of patient episodes in the absence of the medical team ensuring a proactive approach to patient care. In the renal services at St. Mary's Trust, it was decided to develop individualized clinical management plans to include not only those patients seen in the pre-dialysis clinic but also those patients receiving haemodialysis, peritoneal dialysis, day case procedures and transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In both empirical research and anecdotal papers, it appeared that SP by nurses was being introduced in many areas of practice, both in primary and secondary care. The most commonly identified area of research involved mental health [37,38,45] but literature relating to other clinical areas was identified, including renal services [50], rheumatology [51], dermatology [52], epilepsy [53] and substance misuse [54]. James [36] describing her methodologically limited study of diabetic inpatients, reported that patients experienced less medication delays, less variation in attending staff and increased liaison between SP nurse and ward staff and no prescription errors.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In both empirical research and anecdotal papers, it appeared that SP by nurses was being introduced in many areas of practice, both in primary and secondary care. The most commonly identified area of research involved mental health [37,38,45] but literature relating to other clinical areas was identified, including renal services [50], rheumatology [51], dermatology [52], epilepsy [53] and substance misuse [54]. James [36] describing her methodologically limited study of diabetic inpatients, reported that patients experienced less medication delays, less variation in attending staff and increased liaison between SP nurse and ward staff and no prescription errors.…”
Section: Clinical Applicationsmentioning
confidence: 99%